2015
DOI: 10.3892/etm.2015.2467
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory functions of Houttuynia cordata Thunb. and its compounds: A perspective on its potential role in rheumatoid arthritis

Abstract: Abstract. The aim of this review was to take a look at the anti-inflammatory functions of Houttuynia cordata Thunb. (HCT) that have been illustrated in the literature and to explore new fields in which HCT could be used in the future. The use of HCT has been described in broad inflammatory domains, where it has exhibited a variety of activities, including antiviral, antibacterial, antiparasitic and immunostimulant activity, with high efficiency, mild features and definite therapeutic effects. The numerous anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…In our study, the levels of both serum and fecal endotoxin as well as serum TNF-α and IL-1β concentrations in the metformin + HCE group were significantly lower than those in the metformin group, indicating that the anti-inflammatory activity of Houttuynia cordata is stronger than that of metformin. It was reported that Houttuynia cordata supercritical extract (HSE) was able to reduce the production of TNF-α and prostaglandin E2 (PGE2) in a carrageenan-air pouch model of inflammation in mice, suggesting that HSE exerts anti-inflammatory effects by inhibiting TNF-α and cyclooxygenase 2 (COX-2)-PGE2 pathways [ 42 ]. Using lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages as an in vitro inflammatory model, it was shown that ethyl acetate fraction of Houttuynia cordata extract (HCE-EA) downregulated nitric oxide (NO), PGE2, TNF-α, and IL-6 production, as well as inducible nitric oxide synthase (iNOS) and COX-2 expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the levels of both serum and fecal endotoxin as well as serum TNF-α and IL-1β concentrations in the metformin + HCE group were significantly lower than those in the metformin group, indicating that the anti-inflammatory activity of Houttuynia cordata is stronger than that of metformin. It was reported that Houttuynia cordata supercritical extract (HSE) was able to reduce the production of TNF-α and prostaglandin E2 (PGE2) in a carrageenan-air pouch model of inflammation in mice, suggesting that HSE exerts anti-inflammatory effects by inhibiting TNF-α and cyclooxygenase 2 (COX-2)-PGE2 pathways [ 42 ]. Using lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages as an in vitro inflammatory model, it was shown that ethyl acetate fraction of Houttuynia cordata extract (HCE-EA) downregulated nitric oxide (NO), PGE2, TNF-α, and IL-6 production, as well as inducible nitric oxide synthase (iNOS) and COX-2 expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium houttuyfonate also showed potential therapeutic activity for rheumatoid arthritis, which is the destruction of the joint caused by pathological hyperplasia of the synovium. Through in vitro synovial cell experiments, sodium houttuyfonate effectively inhibited the proliferation of synovial cells in a dose-dependent manner within the range of 25 μg/ml∼200 μg/ml ( Li et al, 2014 ; Li and Zhao, 2015 ).…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Decyl acetaldehyde, the main antibacterial active component of Houttuynia cordata Thunb, has an obvious antibacterial effect on a variety of bacteria, acid-fast bacilli and fungi, but its properties are unstable (1)(2)(3). The synthetic sodium bisulfite adduct of decanoylacetaldehyde in China is called synthetic houttuynin and has an obvious antibacterial effect on a variety of gram-positive and negative bacteria (4).…”
Section: Introductionmentioning
confidence: 99%